Clinical Characteristics of Moderate-to-Severe Obstructive Sleep Apnea: A Cross-sectional Analysis of 12,715 Adults from the TURKAPNE Cohort - Balcan B.; Pıhtılı A.; Kıyan E.; Taşbakan M. S.; Başoğlu Ö. K.; Aydın Ş.; ÇİLLİ A.; Dursunoğlu N.; YETKİN N. A.; Peker Y.; et al. (My University, 2026)
OBJECTIVE: Obstructive sleep apnea (OSA) is a common sleep-related breathing disorder associated with cardiometabolic morbidity. However, its clinical presentation is heterogeneous, and subjective sleepiness does not consistently reflect disease severity. We aimed to describe the clinical and polysomnographic characteristics of moderate-to-severe OSA and to identify factors independently associated with disease severity in a large nationwide sleep clinic cohort. MATERIAL AND METHODS: This cross-sectional study was conducted within the Turkish Sleep Apnea Database cohort and included 12,715 adults with complete baseline clinical and polysomnographic data from 34 sleep centers. Moderate-to-severe OSA was defined as an apnea-hypopnea index (AHI) >15 events/h. Demographic and anthropometric variables, sleep-related symptoms, Epworth Sleepiness Scale (ESS) scores, polysomnographic parameters, and comorbidities were analyzed. Independent factors associated with moderate-to-severe OSA were identified using multivariable logistic regression. RESULTS: Overall, 8,393 patients (66.0%) had moderate-to-severe OSA and 4,322 (34.0%) had no or mild OSA (AHI 11) was more common (25.8% vs. 17.7%, P < 0.001), ESS score was not independently associated with disease severity. Increasing age, male sex, higher BMI, snoring, witnessed apneas, and nocturnal dyspnea remained independent associates of moderate-to-severe OSA. CONCLUSION: In this large nationwide sleep clinic cohort, objective risk factors and classic nocturnal symptoms were more informative than subjective sleepiness in identifying clinically significant OSA and support a risk-based approach in routine pulmonary practice.
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Solunum Sistemi; Clinical Medicine (Med); Clinical Medicine; Respiratory System; Akciğer ve Solunum Tıbbı; Pulmonary and Respiratory Medicine; comisa; Insomnia; polysomnography; sleep apnea